Medical X-RAY Image Classification Using CNN Based Model - Prashant Patil; Chetan More; Vedant Bajirao (Vidhyayana - An International Multidisciplinary Peer-Reviewed E-Journal - ISSN 2454-8596, 2023)
Viruses, bacteria, and fungus may all cause pneumonia, which one among the primary reasons of mortality in the globe. Detecting pneumonia from chest X-rays is challenging, however, this work is about simplifying the procedure for both experts and novices using a novel deep learning framework based on transfer learning. Previous studies have proposed a large amount of deep learning models as for pneumonia detection, but finding a successful approach that fulfils all performance measures. Therefore, this work proposes a pre-trained model called ResNet152V2, a Convolutional Neural Network (CNN), and evaluates it using Python. The suggested model outperforms other models in terms of f1-score, area under the curve, precision, accuracy and by 94.65%, 92.85%, 93.94% and 93.27%, respectively. An important goal of this research is to offer effective deep learning model for the identification and categorization of pneumonia.